UNESCO Strategy and Digital Policies for Teacher Training: The Deconstruction of Innovation in Spain - Lourdes Belén Espejo Villar; Luján Lázaro Herrero; Gabriel Álvarez López (Springer, 2022)
This paper examines initial teacher training policies in the context of youth digitalisation. Based on international ICT competency frameworks for teachers (UNESCO, 2008, 2019) and information literacy, MIL (UNESCO, 2011), we analyse how Spanish (public and private) universities represent digital innovation, and the identity practices of young people, linked to hyperconnectivity. Focusing on initial training received by future secondary teachers, the sample was selected according to the criteria of non-presential learning (online, distance, blended) applied in the teacher training process. Results confirm ongoing deficiencies in critical teacher digitalisation management, highlighting certain asymmetries between the categories constructed. Data reveals the prevalence of intervention more geared towards formal knowledge than towards decoding digital grammar (which is how digitalisation is used in education). The paper concludes by advocating convergence strategies as a circular mechanism that must underpin all teacher training policies in the age of hyperconnectivity.